Biocompatibility of PCL/PLGA-BCP porous scaffold for bone tissue engineering applications. Issue 9 (13th June 2017) - Thi Hiep, Nguyen; Chan Khon, Huynh; Dai Hai, Nguyen; Byong-Taek, Lee; Van Toi, Vo; Thanh Hung, Le
Abstract: In this study, biomimic porous polycaprolactone/poly (lactide-co-glycolide) loading biphasic tricalcium phosphate (PCL/PLGA-BCP) scaffolds were fabricated successfully by solvent evaporation method. The distribution of biphasic tricalcium phosphate (BCP) in polycaprolactone/poly (lactide-co-glycolide) (PCL/PLGA) scaffold was confirmed by micro-computed tomography (micro-CT) scanning, scanning electron microscope (SEM) observation and Energy-dispersive X-ray Spectroscopy (EDS) analysis. The hydrophilicity of the scaffolds was confirmed by contact angle measurement. In in vitro experiments, proliferation of human bone marrow mesenchymal stem cell (hBMSCs) and its osteoblastic differentiation on scaffold were assessed for 1, 2 and 3 weeks using 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay, fluorescence observation, hematoxylin & eosin (H&E) staining and real-time polymerase chain reaction (RT-PCR). In in vivo experiments, ossification was observed using micro-CT analysis and histological staining.